Native language, ethnic origin, belonging perception, second language attitudes of bilinguals in Elazig within the context of bilingualism - Eraydin, Yelda Yesildal; Buran, Ahmet (IGI Global, 2024)
The mother tongue of approximately 90 per cent of the population of Turkey is Turkish. The vast majority of this population is monolingual. Speakers of languages such as Kurdish, Zazaki, Arabic, Circassian, Bosnian, Georgian, Laz, Pomak, Albanian, Romani and Hemshish are generally Muslim. Religious unity has been instrumental in strengthening the historical and cultural commonality between these communities and Turks. Our citizens living in the Eastern and Southeastern Anatolia regions of Turkey have a heterogeneous linguistic and identity structure in which no single language has absolute dominance. In this respect, Elazig is a place where bilinguals live together, where Turkish is the biggest common means of understanding and which embodies the language and identity characteristics of the region. In the literature, the study deals with the processes of Turkish-Kurdish and Turkish-Zazaki bilinguals' acquisition and learning of Turkish as a mother tongue with a holistic approach for the first time. © 2025, IGI Global Scientific Publishing. All rights reserved.
Keywords: Albanians; Anatolia; Bilinguals; Holistic approach; Language attitude; Mother tongues; Native language; Second language; Turkishs; Semantics